2008
DOI: 10.4141/cjss07112
|View full text |Cite
|
Sign up to set email alerts
|

Mercury transfer from watersheds to aquatic environments following the erosion of agrarian soils: A molecular biomarker approach

Abstract: Caron, S., Lucotte, M. and Teisserenc, R. 2008. Mercury transfer from watersheds to aquatic environments following the erosion of agrarian soils: A molecular biomarker approach. Can. J. Soil Sci. 88: 801Á811. Lake St. Pierre, an important freshwater location for sports and commercial fisheries in Canada, is composed of a 120 km 2 stretch of the St. Lawrence River, located at the center of the St. Lawrence Lowlands. Receiving its waters from the St. Franc¸ois, Yamaska, Ottawa, and St. Lawrence Rivers, it is sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
0
15
1
Order By: Relevance
“…Several studies have observed that the levels of T-Hg transported to lakes are related to TOM concentration (Driscoll et al 1995;Kolka et al 1999;Kainz et al 2003;Sanei and Goodarzi 2006). More precisely, some studies raised the issue that TOM quality (source, composition), more than the sole quantity of TOM entering the lake, plays a key role in the fate of Hg in the environment Kainz and Lucotte 2006;Sanei and Goodarzi 2006;Caron et al 2008;Ouellet et al 2009). The regime of atmospheric Hg deposition on soil also varies according to vegetation (Schroeder and Munthe 1998;Demers et al 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have observed that the levels of T-Hg transported to lakes are related to TOM concentration (Driscoll et al 1995;Kolka et al 1999;Kainz et al 2003;Sanei and Goodarzi 2006). More precisely, some studies raised the issue that TOM quality (source, composition), more than the sole quantity of TOM entering the lake, plays a key role in the fate of Hg in the environment Kainz and Lucotte 2006;Sanei and Goodarzi 2006;Caron et al 2008;Ouellet et al 2009). The regime of atmospheric Hg deposition on soil also varies according to vegetation (Schroeder and Munthe 1998;Demers et al 2007).…”
Section: Introductionmentioning
confidence: 97%
“…The use of lignin-derived phenols biomarkers to characterize lake water particulate organic matter (POM) and DOM is novel (Weissenberger 2007;Caron et al 2008). The aim of this research is to assess the role of terrigenous OM, using vascular plant-derived biomarkers, on Hg loadings in lakes.…”
Section: Introductionmentioning
confidence: 99%
“…First, it is less assimilated by invertebrates than epiphytes and macrophytes. Second, the MeHg concentrations in SPM are very low (Caron et al 2008), much lower in fact than those of the other OM sources. Third, we found no relationships between SPM proportion in consumer diet and Hg concentrations in the consumers.…”
Section: Links Between Hg Concentrations and Om Sourcesmentioning
confidence: 97%
“…Terrestrial OM inputs, illustrated partly in our study by SPM signature (Caron et al 2008), represented a smaller dietary resource for macroinvertebrate primary consumers in Lake St. Pierre. This is in agreement with a recent study by Clapcott and Bunn (2003), which reported low contributions of C 4 plants to aquatic food webs, despite their widespread distribution and production.…”
Section: Contribution Of the Om Sources To Macroinvertebrate Dietmentioning
confidence: 99%
See 1 more Smart Citation